2006
DOI: 10.1063/1.2266529
|View full text |Cite
|
Sign up to set email alerts
|

Structural transformations of double-walled carbon nanotube bundle under hydrostatic pressure

Abstract: Three kinds of the response mechanisms to the external pressure have been found for doublewalled carbon nanotube (DWNT) bundle, depending strongly on their average radius and symmetry. The small-diameter DWNT bundle undergoes a small discontinuous volume change, and then deform continuously. The intermediate-diameter DWNT bundle collapses completely after a structure phase transition (SPT). Significantly, two SPTs exist for the larger-diameter DWNT bundle if the outer tube has no C 6 or C 3 symmetry. It would … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 32 publications
6
46
0
Order By: Relevance
“…It is found by numerical simulation using the universal force field (UFF) method [70] that there exist three kinds of the response behaviors to external pressure for different DWCNTs. Their loading curves vs. hydrostatic pressure are given in Fig.…”
Section: Dwcnt Bundlesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found by numerical simulation using the universal force field (UFF) method [70] that there exist three kinds of the response behaviors to external pressure for different DWCNTs. Their loading curves vs. hydrostatic pressure are given in Fig.…”
Section: Dwcnt Bundlesmentioning
confidence: 99%
“…In order to have an insight into the relationship of the collapse pressure P d with the DWCNT diameter and its tube symmetry, Yang et al [70] introduced the DWCNT's average radius R ave , which is defined as an average value of the outer and inner tube's radius of DWCNT. The variation of P d with R ave for the DWCNT bundles can be well fitted to ∼ 1/R 3 ave , as shown in Fig.…”
Section: Dwcnt Bundlesmentioning
confidence: 99%
“…Raman spectroscopy has been broadly used to study effects caused by strain, majorly focusing on the G band behaviour on SWNT bundles [74][75][76][77][78][79][80]. Combination of AFM with confocal Raman spectroscopy was made to follow, in situ, the evolution of the SWNT structure with transversal pressure applied to the tube.…”
Section: Pushing the Limits Of Raman Spectroscopy Applications On Sp mentioning
confidence: 99%
“…Several earlier experimental studies (mostly Raman) reported higher critical pressures for the structural transition of the outer tube in DWCNTs as compared to SWCNTs, and this was attributed to the structural support of the outer tube by the inner tube. 7,30,34 The enhanced structural stability of the outer tube was theoretically predicted by Yang et al 35 : For small-diameter (5,5)(10,10) DWCNT bundles (d inner ≈0.68 nm, d outer ≈1.36 nm) a small discontinuous volume change appears at the critical pressure P d =18 GPa, accompanied by a cross sections' change between two deformed hexagons; the collapse to peanut shaped cross sections, however, happens at higher pressure. In contrast, (7,7)(12,12) DWCNT bundles (d inner ≈0.95 nm, d outer ≈1.63 nm) undergo one structural phase transition and collapse at P d =10.6 GPa.…”
mentioning
confidence: 99%